2015
DOI: 10.2196/jmir.3831
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of HONcode Website Conformity Compared to Manual Detection: An Evaluation

Abstract: BackgroundTo earn HONcode certification, a website must conform to the 8 principles of the HONcode of Conduct In the current manual process of certification, a HONcode expert assesses the candidate website using precise guidelines for each principle. In the scope of the European project KHRESMOI, the Health on the Net (HON) Foundation has developed an automated system to assist in detecting a website’s HONcode conformity. Automated assistance in conducting HONcode reviews can expedite the current time-consumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…Therefore, the automated assistance in conducting HONcode reviews can expedite the current time-consuming tasks of HONcode certification and ongoing surveillance. A recent study showed that there is concordance between automated and expert manual compliance detection for the criteria[18]. In this research we have used the electronic system available at: .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the automated assistance in conducting HONcode reviews can expedite the current time-consuming tasks of HONcode certification and ongoing surveillance. A recent study showed that there is concordance between automated and expert manual compliance detection for the criteria[18]. In this research we have used the electronic system available at: .…”
Section: Methodsmentioning
confidence: 99%
“…We used the standard systematic evaluation scheme with 80% of the collection employed to train the system and 20% to assess the algorithm. The Nave Bayes machine learning algorithm with a single word tokenization and a space reduction of 70% was used for the classifier as a result of previous publication work ( (Boyer and Dolamic, 2014;Boyer and Dolamic, 2015) and in this research). The evaluation of the classifier on the remaining 20% of the collection yielded good results for the Complementarity and Date Attribution criteria with a precision of 83% and 94% respectively, and a recall of 95% for both.…”
Section: Motivationsmentioning
confidence: 99%
“…After extensively testing this system with the sample collection, the next logical step was to verify its performance on real life examples, thus comparing it to the current manual HONcode certification process. In the report (Boyer and Dolamic, 2015), we compared the automated detection of the HONcode criteria with a manual process and we obtained mitigated results especially for the Date Attribution and Complementarity criteria. We also identified further research paths to improve our first evaluation in real life settings.…”
Section: Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ad-hoc solutions to support the general public in searching and accessing health information on the Web have been implemented, typically supported by government initiatives or medical practitioner associations, e.g., HealthOnNet.org (HON [11]) and HealthDirect.gov.au, among others. These solutions aim to provide better health information to the general public.…”
Section: Introductionmentioning
confidence: 99%